Perbandingan Kebijakan Sistem Pendidikan di Indonesia dan Thailand - Ida Arina; Deni, Deni Darmawan; Kibrio, Kibrioburiyeva; Dostnazar, Dostnazar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this article is to analyze the concept of education policy issues in Indonesia and Thailand, including the differences and similarities between the two countries. identify the strengths and weaknesses of education policies in Indonesia and Thailand, so that effective solutions can be found to improve the quality of education in both countries. develop recommendations for effective education policies for Indonesia and Thailand, so that they can improve the quality of education in both countries. This research method uses a qualitative approach with the type of Library Research research, namely data taken from journals, books, documents and online literature. The data technique of this research comes from books, journals and scientific articles related to the comparison of the Thai and Indonesian education systems. Data analysis in this study uses Content Analysis technology, namely classifying or grouping data separately related to the discussion of several of several references, then describing, discussing and criticizing them. In addition, classify similar data and analyze the content critically to obtain specific and adequate results. A comparison of education system policies in Indonesia and Thailand shows that both countries have different strengths and weaknesses. Indonesia has strengths in increasing access to education, curriculum development, and improving teacher quality. However, Indonesia still faces weaknesses in limited resources, implementation difficulties, and uneven quality of education. Thailand has strengths in technology development, improving teacher quality, and curriculum development. However, Thailand still faces weaknesses in limited access to education, implementation difficulties, and uneven quality of education.